2001
DOI: 10.1001/archsurg.136.9.996
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Cardiac Morbidity and Mortality After Endoluminal Abdominal Aortic Aneurysm Repair

Abstract: Hypothesis: The adverse cardiac event rate following endoluminal abdominal aortic aneurysm (EAAA) repair has decreased as experience in performing the procedure has increased. Aneurysm complexity affects the rate of adverse cardiac events. Design and Patients: Data from 173 consecutive patients undergoing EAAA repair from 2 successive periods were compared. There were 82 patients in the early group (group 1) and 91 patients in the later group (group 2). Main Outcome Measures: Myocardial infarction, congestive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In total, 3392 publications were retrieved from the initial systematic literature search (Supplementary Table I, online only) and 21 publications were obtained by the manually computer-aided bibliographic search from the earlier review. After removing duplicates, screening titles/abstracts and reviewing full-texts, 32 studies met the selection criteria and were included in this meta-analysis, 7,8,[13][14][15][16][17][18][19][20][21][22][23][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] three studies of which were verified by obtaining data through contact with the authors. 29,32,36 Four studies reported independent data for both intact AAA and ruptured AAA, which were separated into two different cohorts.…”
Section: Study Selection and Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 3392 publications were retrieved from the initial systematic literature search (Supplementary Table I, online only) and 21 publications were obtained by the manually computer-aided bibliographic search from the earlier review. After removing duplicates, screening titles/abstracts and reviewing full-texts, 32 studies met the selection criteria and were included in this meta-analysis, 7,8,[13][14][15][16][17][18][19][20][21][22][23][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] three studies of which were verified by obtaining data through contact with the authors. 29,32,36 Four studies reported independent data for both intact AAA and ruptured AAA, which were separated into two different cohorts.…”
Section: Study Selection and Description Of Included Studiesmentioning
confidence: 99%
“…29,32,36 Four studies reported independent data for both intact AAA and ruptured AAA, which were separated into two different cohorts. 30,33,35,39 Finally, we analyzed a total of 36 cohorts (Fig 1), in which 25 cohorts investigated intact AAA, 7,8,[13][14][15][16][17][18][20][21][22][23][28][29][30][31][33][34][35][39][40][41][42]44,45 7 investigated ruptured AAA, 19,30,32,33,35,36,39 and 4 investigated indeterminate AAA. 37,38,43,46 All cohorts were from retrospective studies without high risk bias assessed by Newcastle-Ottawa Scale (Supplementary Table II, online only), 13 cohorts of which were multiple-center studies.…”
Section: Study Selection and Description Of Included Studiesmentioning
confidence: 99%
“…Berge et al 31 Ting et al 52 Azizzadeh et al 53 Biebl et al 54 Leon et al 36 Lifeline 20 Zarins et al 55 Sampaio et al 56 Criado et al 57 Elkouri et al 58 Nordness et al 59 Parlani et al 60 Shames et al 61 Slovut et al 62 Wyers et al 63 Sanchez et al 64 Wolf et al 65 1 1·54 1·22 Howell et al 66 Mathison et al 67 Romero et al 68 Cao et al 69 Pooled odds ratio 35 23 82 80·8 8 2 ·2 68 65 2 (9) 9 (11) Leon et al 36 2746 7974 73·2(8·0)# 71·4(8·0)# --225 (8·2)** 415 (5·2)** Lifeline 20 69 37 42 177 69·9 ‡ 69·9 ‡ --5 (12)** 3 (1·7)** Urbonavicius et al 38 17 52 ----3 (18) 5 (10) Rigberg et al 9 18 71 ----0 (0)** 0 (0)** Sasaki et al 39 11 89 71 ‡ 71 ‡ 57·9(10·2) ‡ 57·9(10·2) ‡ 0 (0)** 1 (1)** Stenbaek et al 40 109 488 71(6·4) 70 (7) --12 (11·0) § 42 (8·6) § Biancari et al 41 239 42 68 90 70·3 ‡ 70·3 ‡ 58 ‡ 58 ‡ 1 (1) 4 (4) Rayan et al 43 100 321 74·4(7·1) ‡ 74·4(7·1) ‡ --2 ( 2 ·0)** 5 (1·6)** Alonso-Pérez et al 44 13 170 77 ‡ 77 (2)…”
Section: Favours Women Favours Menmentioning
confidence: 99%
“…Berge et al 31 17 119 ----1 (6) 3 (2·5) Ting et al 52 15 85 75(7) ‡ 75(7) ‡ 62(8) ‡ 62(8) ‡ 0 (0)** 2 (2)** Azizzadeh et al 53 58 340 73 ‡ 73 ‡ --1 (2) 4 (1·2) Biebl et al 54 40 326 74 (7) 73 (8) --0 (0) 4 (1·2) Leon et al 36 295 1384 73·2(8·0)# 71·4(8·0)# --15 (5·1)** 24 (1·7)** Lifeline 20 235 1828 76·4(7·7) 72·8(7·8) 55·8(10·2) ‡ 55·8(10·2) ‡ 5 (2·1) ¶ 27 (1·5) ¶ Zarins et al 55 23 289 70(7) ‡ 70(7) ‡ 50(3) ‡ 50(3) ‡ 0 (0) 6 (2·1) Sampaio et al 56 29 212 79·9(1·1) 74·9(0·5) 54·1(1·1) 55·5(0·8) 2 (7) 2 (0·9) Criado et al 57 24 216 75·5 ‡ 75·5 ‡ --0 (0) 0 (0) Elkouri et al 58 11 89 76(7) ‡ 76(7) ‡ 58(11) ‡ 58(11) ‡ 0 (0) 0 (0) Nordness et al 59 17 101 75·1(9·4) 73 (7) 61·9(11·6) 57·5(9·7) 2 (12) 0 (0) Parlani et al 60 25 377 75·3 7 1 ·3 5 2 ·2 5 0 ·8 0 (0) 5 (1·3) Shames et al 61 42 203 76(6) 72 (7) --1 (2) 3 (1·5) Slovut et al 62 27 143 73·6(7·2) ‡ 73·6(7·2) ‡ 55(8) ‡ 55(8) ‡ 0 (0) 2 (1·4) Wyers et al 63 34 168 74(7) ‡ 74 (7) ‡ --0 (0) 1 (0·6) Sanchez et al 64 22 133 76·3(6·4) 72·0(7·2) 54·1 5 6 ·7 1 (5) 4 (3·0) Wolf et al 65 26 163 77·9(6·3) 73·1(8·1) 57·2(10·9) 57·8(9·4) 0 (0) 2 (1·2) Howell et al 66 23 192 72(8·2) ‡ 72(8·2) ‡ 55·5(11) ‡ 55·5(11) ‡ 0 (0) 0 (0) Mathison et al 67 24 281 75·9(6·7) 74·4(7·9) 52·1(6·8) 57(11·8) 0 (0) ‡ ‡ 8 (2·8) ‡ ‡ Romero et al 68 17 156 73 ‡ 73 ‡ 58 ‡ 58 ‡ 1 (6) ¶ 5 (3·2) ¶ Cao et al 69 10 105 69·8(7) ‡ 69·8(7) ‡ --0 (0) 0 (0) mean AAA diameter stratified by sex ( Table 1) 34,35 . For the elective EVAR group, the majority of the studies reported mean AAA diameter (13 of 21) and six of these stratified by sex; mean AAA diameter was 55·5 mm for women and 55·4 mm for men.…”
Section: Endovascular Repairmentioning
confidence: 99%
“…Results of retrospective clinical studies suggest that surgical trauma induced at a remote site may have deleterious effects upon MI [23,24]. In fact, patients recovering from surgery to repair abdominal aortic aneurysm have a significantly higher risk for MI, and on average have larger infarcts and increased mortality relative to those not having undergone such surgery [23][24][25]. We observed that infarct size after in vivo ischemia/reperfusion (I/R) was increased by remote nonischemic vascular surgery performed to catheterize the carotid artery for blood pressure measurements, a phenomenon we call remote cardiac I/R injury (RCI).…”
Section: Introductionmentioning
confidence: 99%